The effect of CSR disclosure on tax avoidance through earnings management: Indonesian evidence - Rahma Maulida Wanda Azahra; Sri Handayani (Journal of Contemporary Accounting, 2022)
This study aims to explain the effect of CSR disclosure on tax avoidance and analyze that effect through earnings management. Companies use CSR expenditure as an earning management strategy. CSR expenditure is assessed as a deductible expense to obtain low taxes. This strategy, called earnings management, is the first step of tax avoidance. The population was taken from companies listed on the Indonesia Stock Exchange (IDX) in the Consumer Non-Cyclicals sector from 2018-2020. Sampling uses a purposive sampling technique with 25 companies. The analysis used is multiple linear regression with the intervening variable testing using the Sobel test. The results of this study explain that CSR disclosure has a negative effect on tax avoidance. Wide CSR disclosure means the company is far from tax avoidance practices. Testing using the intervening variable results in earnings management being unable to mediate the effect of CSR disclosure on tax avoidance.